2021
DOI: 10.4103/jmas.jmas_142_20
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection for low rectal cancer in a patient with horseshoe kidney – Technical considerations to prevent iatrogenic injuries

Abstract: Horseshoe kidney (HSK) is a rare congenital malformation of the kidneys and is commonly associated with other anomalies of the renovascular and ureteropelvic systems. These anomalies present a surgical challenge, especially for surgeries involving the retroperitoneum. We present the case of a 56-year-old male patient with biopsy-proven rectal cancer who had completed neoadjuvant chemoradiation and was planned for curative resection. Contrast-enhanced computed tomography (CECT) of the abdomen and pelvis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Abnormalities of renal artery have sometimes been reported to branch off the aorta, iliac artery, or IMA and care should be taken not to damage them during medial dissection to maintain blood flow, and the site of IMA ligation should also be considered occasionally. 1,2 The ureter and gonadal arteriovenous vessels are reported to often travel anterior to the kidney, although cases involving abnormal running of the ureter or duplicate ureters have been reported. Placement of a fluorescent ureteral catheter to prevent intraoperative ureteral injury has been recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormalities of renal artery have sometimes been reported to branch off the aorta, iliac artery, or IMA and care should be taken not to damage them during medial dissection to maintain blood flow, and the site of IMA ligation should also be considered occasionally. 1,2 The ureter and gonadal arteriovenous vessels are reported to often travel anterior to the kidney, although cases involving abnormal running of the ureter or duplicate ureters have been reported. Placement of a fluorescent ureteral catheter to prevent intraoperative ureteral injury has been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Although the magnifying effect of the scope is promising for dissection and identification of the dissected layer, the use of straight forceps and the restricted approach direction during surgery require caution when manipulating around the IMA root and interfere with the medial approach due to the protrusion of the descending renal parenchyma and isthmus. 1,2 Robot-assisted surgery with the Da Vinci surgical system has a three-dimensional video imaging system and a flexible arm, which may be useful in understanding fine anatomy and protecting organs. [7][8][9] In the present case, the visibility of the hypogastric nerve was excellent, and the nerve traveled anterior to the kidney, confirming preservation of the nerve all the way to the IMA root.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [33] also presented a novel variation identified during routine dissection in which the posterior division of the femoral nerve was penetrated by the ascending branch of the lateral circumflex femoral artery. Preoperative medical scans helped Vigneshwaran and his colleagues [34] to identify double variations of a horseshoe kidney and an accessory renal artery in a challenging case of low rectal cancer planned for laparoscopic resection. In addition, during preoperative diagnosis of a living liver donor, Gündoğdu and Kebapçı [35] observed an accessory right hepatic artery originating from the dorsal pancreatic artery and a middle hepatic artery arising from the pancreaticoduodenal artery.…”
Section: Approaches To Identifying Anatomical Variationsmentioning
confidence: 99%
“…In addition, during preoperative diagnosis of a living liver donor, Gündoğdu and Kebapçı [35] observed an accessory right hepatic artery originating from the dorsal pancreatic artery and a middle hepatic artery arising from the pancreaticoduodenal artery. These preoperative observations of anatomical variations guided the surgeons to safe surgical resection of the cancer, and they searched for a new liver donor [34,35].…”
Section: Approaches To Identifying Anatomical Variationsmentioning
confidence: 99%